Flexible micro temperature, voltage and current sensors for local real-time microscopic diagnosis inside high temperature proton exchange membrane fuel cell stack. (August 2017) - Lee, Chi-Yuan; Chiang, Yu-Chun; Weng, Fang-Bor; Li, Shih-Chun; Wu, Pai-Hsuan; Yueh, Heng-I.
Abstract: The local temperature, voltage and current nonuniformity in the high temperature proton exchange membrane fuel cell (HT-PEMFC) stack can accelerate the aging of membrane electrode assembly (MEA) and the failure of overall fuel cell stack. This study used micro-electro-mechanical systems (MEMS) technology to integrate micro temperature, voltage and current sensors into a 40 μm thick stainless steel substrate successfully, and selected the temperature tolerant and electrochemical corrosion resistant polyimide (PI) as protective layer. This flexible micro sensor is characterized by multiple functions, compactness, corrosion resistance, good temperature tolerance, quick response, real-time measurement and optional location. Flexible micro sensor embedded in the high temperature fuel cell stack, the effect on the performance of fuel cell stack was less than 1%. This study used NI PXI 2575 data acquisition unit for real-time microscopic diagnosis of local temperature, voltage and current information at 150 °C operating temperature and constant current (5, 15, 30 A) inside the high temperature fuel cell stack, and found that the nonuniform temperature distribution in the fuel cell stack resulted in nonuniform voltage and current distributions and hot stack. Highlights: Home-made three-in-one flexible micro sensor can be placed anywhere in a high temperature proton exchange membrane fuel cell stack. Three-in-one flexible micro sensors are three functions, compactness, acid corrosion resistance, good temperature tolerance, quick response, real-time measurement and optional location. In-situ diagnosis local temperature, voltage and current information of a high temperature proton exchange membrane fuel cell stack.